Atomic- and Molecular-Level Modulation of Dispersed Active Sites for Electrocatalytic CO2 Reduction - Methasit Juthathan (2022)
Global climate changes have been impacted by the excessive CO2 emission, which exacerbates the environmental problems. Electrocatalytic CO2 reduction (CO2RR) offers the solution for utilising CO2 as feedstocks for value-added products while potentially mitigating the negative effects. Owing to the extreme stability of CO2, selectivity and efficiency are crucial factors in the development of CO2RR electrocatalysts. Recently, single-atom catalysts have emerged as potential electrocatalysts for CO2 reduction. They generally comprise of atomically- and molecularly dispersed active sites over conductive supports, which enable atomic-level and molecular-level modulations. In this minireview, catalyst preparations, principle of modulations, and reaction mechanisms are summarised together with related recent advances. The atomic-level modulations are first discussed, followed by the molecular-level modulations. Finally, the current challenges and future opportunities are provided as guidance for further developments regarding the discussed topics.